Norms, self-interest and effectiveness: explaining double standards in EU reactions to violations of democratic principles in Sub-Saharan Africa - Del Biondo, Karen (Afrika Focus, 2012)
Democracy promotion is often criticized for its double standards: in some countries, negative measures (public criticism, sanctions) are used, while in other countries there is a preference for positive measures (incentives, dialogue and capacity building). While such double standards have also been observed in European Union (EU) policies (Brummer, 2009; Warkotsch, 2008), few studies have thoroughly investigated the reasons for these double standards, particularly in Sub-Saharan Africa.